Effect of supplementation of shrimp waste on the immune response, lipid profile and carcass characters of cross bred pigs - M. Yugandhar Kumar; J.V. Ramana; A. Ravi; J. Suresh; A.V.N. Sivakumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A study was conducted to determine the effects of supplementation of shrimp waste containing chitosonon the immune response, lipid profile and carcass characters of cross bred pigs. 40 weaned piglets (42 days) were assigned at random to 5 dietary treatments. The standard grower ration (T1) was supplemented with chlorotetracyclin (T2)while shrimp shell meal was included at 2.5% (T3), 5.0% (T4) and 7.5% (T5), as a source of chitosan. The feed and water was made adlibitum. There was a significant increase (P < 0.01) in serum total protein, primarily due to improvement in the globulin concentration, decrease (P<0.01) in serum total cholesterol, serum triglycerides, LDL Cholesterol and increase in HDL cholesterol due to shrimp waste supplementation and there was no significant difference among the pigs fed different treatments for the various carcass characters.